(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Analytical research from the standpoint of leadership courses at the University of Kufa the Objective of current research to measure the impact of the dimensions of intelligence strategic of in (the future vision, partnership or strategic alliance, the ability to motivate staff, intuition, Innovation Strategic) in the decision-making process and strategic objective ( in educational tasks, administrative tasks, the field of practice decision) and stand on the nature of the impact of prevailing in a society which is to research and leadership of the University of Kufa and boards of faculties. The resolution was used as a tool head for data collection and distribution to the research community by (142) to identify. Was recovered (131) identifying valid for analysis, two main hypotheses have been formulated as to find that a relationship between the legal entities and the impact of the effectiveness of the strategic dimensions of intelligence in the exercise of strategic decision-making process. And after obtaining the data was statistically using a set of methods from this a multiple linear regression, was reached on the results and a number of conclusions a "effectiveness of the dimensions of intelligence strategic role of the cosplay in the strategic decision on the research community," and also included a number of recommendations which referred to the need to recruit dimensions of intelligence in the strategic decision-making process.